ZONE BASED SECURED ENERGY EFFICIENT MECHANISM IN WIRELESS SENSOR NETWORKS FOR EFFICIENT COMMUNICATION - Kumar, Pankaj; Singh, Ramanjeet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Wireless sensor network has revolutionized the way computing and software services are delivered to the clients on demand. Wireless sensor network is very important to the mankind. It consist of number of sensor called nodes and a base station. Nodes collect data and send to the base station. There are number of nodes which send data at a time. So, number of problems are occurred. Usually the WSNs are automated, that is they work without the human intervention. In such cases it becomes very crucial that the network must have the capability of self-healing security mechanism to handle with all the types of attacks. Without the use of security mechanism, the data can be altered or hacked by some intruder in the network. The nodes are connected with each other without a wired connection through the base stations, they are highly prone to the hacking attacks. WSNs are used to sense various environmental or other parameters which can be used to predict natural hazards, climatic changes or other types of data analysis. During the periods when the WSN nodes are in working condition, they need secure cryptographic keys for secure propagation of the sensitive information. The present research is focused on the design of energy efficient security mechanism for improved reliability in sensor based environment. The RSA encryption algorithm has used for encryption purposes.